Counter-terrorism measures and perceptions of police legitimacy: The importance Muslims place on procedural justice, representative bureaucracy, and bounded-authority concerns - Ali, Mohammed M. (Journal of criminology, 2022)
Engaging Muslims in counter-terrorism (CT) has proved challenging for police worldwide. Some research has focussed on the utility of police being procedurally just in their CT strategies to enhance their legitimacy and subsequent cooperation from Muslims. Despite the efficacy of procedural justice, however, some have argued that procedural justice scholarship is too narrowly focussed on how police treat citizens. Citizens? concerns about police acting within the limits of appropriate power (i.e., ?bounded-authority? concerns), as well as representativeness in policing (i.e., ?representative bureaucracy?), can also influence citizens? judgments of police legitimacy. This study explores how, when, and why procedural justice, bounded authority, and representation concerns shape Muslims? perceptions of police CT measures and police legitimacy. Using focus group data from 104 Australian-Muslims, results revealed that CT measures that include Muslims as partners in terrorism prevention and those that draw on principles of procedural justice were perceived most favourably, and were seen to promote police legitimacy. Measures that were condemned were perceived as bounded-authority violations and damaged police legitimacy. Implications for theory and police practice are discussed.